Histidine 375 Modulates CD4 Binding in HIV-1 CRF01_AE Envelope Glycoproteins - Zoubchenok, Daria (J Virol, 2017)
The envelope glycoproteins (Envs) from human immunodeficiency virus type 1 (HIV-1) mediate viral entry. The binding of the HIV-1 gp120 glycoprotein to CD4 triggers conformational changes in gp120 that allow high-affinity binding to its coreceptors. In contrast to all other Envs from the same phylogenetic group, M, which possess a serine (S) at position 375, those from CRF01_AE strains possess a histidine (H) at this location. This residue is part of the Phe43 cavity, where residue 43 of CD4 (a phenylalanine) engages with gp120. Here we evaluated the functional consequences of replacing this residue in two CRF01_AE Envs (CM244 and 92TH023) by a serine. We observed that reversion of amino acid 375 to a serine (H375S) resulted in a loss of functionality of both CRF01_AE Envs as measured by a dramatic loss in infectivity and ability to mediate cell-to-cell fusion. While no effects on processing or trimer stability of these variants were observed, decreased functionality could be linked to a major defect in CD4 binding induced by the replacement of H375 by a serine. Importantly, mutations of residues 61 (layer 1), 105 and 108 (layer 2), and 474 to 476 (layer 3) of the CRF01_AE gp120 inner domain layers to the consensus residues present in group M restored CD4 binding and wild-type levels of infectivity and cell-to-cell fusion. These results suggest a functional coevolution between the Phe43 cavity and the gp120 inner domain layers. Altogether, our observations describe the functional importance of amino acid 375H in CRF01_AE envelopes. IMPORTANCE A highly conserved serine located at position 375 in group M is replaced by a histidine in CRF01_AE Envs. Here we show that H375 is required for efficient CRF01_AE Env binding to CD4. Moreover, this work suggests that specific residues of the gp120 inner domain layers have coevolved with H375 in order to maintain its ability to mediate viral entry.